First person – Kristin Ates (Disease Models & Mechanisms, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Kristin Ates is first author on ‘ Deficiency in the endocytic adaptor proteins PHETA1/2 impairs renal and craniofacial development’, published in DMM. Kristin is an MD/PhD student in the lab of Y. Albert Pan at Augusta University, Augusta, GA, USA, investigating the underlying pathogenesis of endosomal and lysosomal diseases.